(untitled) (Journal of Economic Research & Business Administration, 2015)
Insurance represents the relation on property protection of interests of natural and legal entities of the certain insured events (insured) at approach by means of payment of insurance compensations for the account of the monetary funds formed by insurers of insurance payments paid to them by insurers, and also from other sources which haven’t been forbidden by the legislation. Economic development of the country is inevitably accompanied by increase in a range of risks and, therefore, expansion of requirements for insurance. Experience of development of a market economy testifies to need of state regulation of activity of economic subjects. Told treats and insurance. Insurance, as well as any activity, without modern acts, the strong and stable legal and regulatory base concerning an order of the organization and activity of insurers, loses meaning in rigid market economy. This sphere can’t do without public administration and regulation and now.